Perfectionism and dignity. (3rd February 2021) - Gilabert, Pablo
Abstract: Perfectionism about well‐being is, at a minimum, the view that people's lives go well when, and because, they realize their capacities. It is common to link perfectionism with an idea of human essence or nature, to view well‐being as the unfolding of characteristically human capacities. This article argues that perfectionism would be more plausible if it abandons reliance on the idea of human nature and focuses instead on the unfolding of some valuable capacities that need not be unique to, or shared by all human beings. The article develops this revised perfectionism through the dignitarian approach—the view that we have reason to organize our personal and social life in such a way that we respond appropriately to the valuable features of individuals that give rise to their dignity. According to the resulting proposal—Dignitarian Perfectionism—human individuals' well‐being consists, at least in part, in developing and exercising the capacities at the basis of their dignity. Dignitarian Perfectionism is evaluative all the way down, pragmatic but not unprincipled, and holistic. Furthermore, it can make sense of the role of some generalizations that animated some of the plausibility of traditional perfectionism—and this without the pitfalls of reliance on an idea of human nature.